Doomscrolling and mental well-being among university students: A qualitative study of late-night digital behavior - Hengki Yandri; Deltia Ismanidar; Dosi Juliawati; Daflaini Daflaini; Rasmita Rasmita; Darsi Darsi; Yatti Fidya (Universitas Ahmad Dahlan, 2026)
Doomscrolling has evolved beyond a mere habit into a significant maladaptive behavior that systematically erodes the mental well-being of university students. This study explores the nexus between late-night compulsive content consumption and the degradation of psychological health. Employing a qualitative approach, the research focuses on seven purposively selected informants exhibiting extreme device usage (>5 hours/day). This sample size was intentionally curated to achieve phenomenological depth and data saturation, ensuring a rich, granular understanding of the digital experience that large-scale surveys often overlook. Data were gathered through participant observation and in-depth interviews, subsequently analyzed using thematic coding to identify recurring behavioral patterns. The findings reveal that informants spend 3 to 5 hours nightly in a